Expression of Selected Inflammatory Cytokine Genes in Bladder Biopsies - Sim, Edmund U. H.; Nur Diana, Binti Anuar; Teng-Aik, Ong; Guan-Chou, Teh (Universiti Malaysia Sarawak (UNIMAS), 2013)
Besides the deregulation of oncogene and tumour suppressor gene, bladder carcinoma can also be caused by inflammation. To date, the association of inflammatory cytokines with carcinoma of the bladder (especially the transitional cell carcinomas) is not fully understood. In this study, we report an attempt to examine expression patterns of pro- and anti- inflammatory cytokine genes from normal and tumour tissue biopsies of the human bladder. Our molecular assays involved the use of the GeneXP™ Human Cyto-3 kit and the Reverse Transcription – Polymerase Chain Reaction test. Due to limitation in our experimental process, mainly attributed by inconsistencies in the results obtained between the two assay systems, we cannot reach a conclusion regarding the association of the six selected inflammatory cytokine genes (IL-8, IL-12A, IL-18, TGF-β1, TGF- β2, and TGF-β3) with bladder carcinoma. However, our data provided early novel evidence of expression of four inflammatory cytokine genes, namely IL-12A, TGF-β1, TGF-β2, and TGF-β3 in tissues derived from the human bladder.